S3-4: The Tilt Aftereffect and Position-Shift Illusions - Ikuya Murakami (i-Perception, 2012)
After prolonged viewing of tilted bars, subsequently viewed upright bars appear to be inclined oppositely. This tilt aftereffect is believed to involve population coding of orientation by various orientation-selective units interacting with each other, but it is unknown at what stage of shape processing pathway these neural interactions take place. We recently conducted psychophysical experiments to assess the relationship between this adaptable process and the underlying mechanisms of position-shift illusions including the flash-lag effect and the flash-drag effect. In these motion-related position phenomena, the perceived position of a briefly flashed stimulus is altered by the presence of a moving stimulus nearby, and as such, the subjective orientation seen in a specially designed stimulus can be tilted even though each stimulus component stays upright. We found that adaptation to this subjective tilt yielded no tilt aftereffect, demonstrating functional independence between the orientation and position mechanisms.